Recovery time and predictors of severe acute malnutrition in children aged 6-59 months via an outpatient therapeutic program in Borena zone: A prospective cohort study. - Girma Tenkolu Bune; Abuna Mohammed; Samrawit Hailu; Eden Ashenafi (PLoS ONE)
Background Severe acute malnutrition (SAM) is a severe condition causing bilateral pitting edema or signs of wasting in children, with a high mortality risk. An outpatient therapeutic program is recommended for managing SAM children without complications, but there is limited information on recovery time and its determinants. Objective This study aims to assess the time to recovery and its predictors among children aged 6-59 months with SAM admitted to the Outpatient therapeutic program in the Borena zone, Oromia region, Southern Ethiopia in 2023. Methods A prospective follow-up study was carried out from March 1-30, 2023, on 322 children aged 6-59 months in health facilities in the Borena zone. After being collected using a structured questionnaire, the data was imported into Epi Data Manager version 3.1 and exported to SPSS version 26 for analysis. Model fitness was assessed using the log rank test, and time-to-recovery from SAM was found to be predicted by Cox regression analysis. Lastly, the study used the Adjusted Hazard Ratio with a p-value < 0.05 and a 95% confidence interval to describe the connection. Results The median duration for recovery was found to be 42 days with an interquartile range of 35 to 49. Children who received Amoxicillin had a four-times higher recovery rate (AHR = 4.09; 95% CI: 2.75, 6.07). The presence of diarrhea prolonged the recovery time by 53.0% (AHR = 0.47; 95% CI: 0.36, 0.62), while vomiting prolonged the recovery time by 58.0% (AHR = 0.42; 95% CI: 0.32, 0.55). Edema reduced the chances of recovery by 48% (AHR = 0.52; 95% CI: 0.36, 0.62). Conclusion The study found that recovery time for children with severe acute malnutrition is consistent with prior research. Key factors influencing recovery duration include the prompt administration of Amoxicillin upon admission and the presence of symptoms like diarrhea, vomiting, and edema. The findings emphasize the critical role of specific symptoms in predicting recovery times for children with SAM. By understanding these relationships, healthcare providers can enhance treatment strategies, improve resource management, and ultimately contribute to better health outcomes for affected children.